THE ROLE OF MEDIA DISCLOSURE IN ENHANCING THE FINANCIAL PERFORMANCE OF THE IRAQI BANKING SECTOR - Ahmed Majid Zaidan; Zeyad Sami Abed; Nuha Safi Abd (Scholar Express Journals, 2023)
The research aims to study the role of advertising expenditures disclosed – in the financial statements of the Iraqi banking sector and published in the Iraq Stock Exchange – in enhancing financial performance represented by accounting standards, which include return on sales (ROS), return on assets (ROA), and return on equity (ROE) during the period (2012–2021). In this research, the researchers used the correlation between advertising expenditures and the financial performance of banks, to verify the long-term effect of advertising expenditures on the financial performance of the Iraqi banking sector. The results indicate that advertising expenditure has a positive effect on financial performance represented by (ROA) and (ROE) at a statistical significance level of (5%). On the other hand, there is no significant effect of advertising expenditure on the rate of (ROS) as a proxy for financial performance. However, in terms of the relationship, it was found that an increase or decrease in advertising expenditure is not chaperoned by a significant increase or decrease in the rate of (ROS). Conversely, an increase or decrease in advertising expenditure is chaperoned by a significant increase or decrease in the rate of (ROA) and the rate of (ROE). Despite there are many studies and research on advertising and its effect on the financial position of companies, there are only a few studies that examine the effect of advertising expenditures on the financial performance of the banking sector. Therefore, this research has the ability to highlight studies related to the banking sector marketing aspect.
Keywords: Advertising Expenditures; Financial Performanc; Return on Sales